Defleksi Lateral Tiang Tunggal Akibat Beban Lateral pada Tanah Pasir - Ahmad Fahrul Lafit; Togani Cahyadi Upomo; Yeri Sutopo; Agung Sutarto (Universitas Negeri Yogyakarta, 2021)
ABSTRACTOne type of deep foundation is a pile foundation that is designed and has the ability to withstand axial, lateral, and uplift loads. This analysis aims to determine and compare deflections that occur on poles that are in granular soil by using the manual calculation of the p-y curve method with finite difference approaches and calculations with Allpile and Plaxis software. The analysis was conducted three times, namely on a 60 cm diameter pole at a depth of 10 meters embedded pile with lateral loads of 25 kN, 50 kN, and 75 kN. The data used to calculate the lateral deflection of the pole is secondary data. Lateral deflection analysis using Plaxis software with a load of 25 kN, 50 kN, and 75 kN obtained lateral deflection of the uppermost pole respectively 0.159 cm, 0.324 cm, and 0.545 cm. Lateral deflection analysis using Allpile software with a load of 25 kN, 50 kN, and 75 kN obtained lateral deflection of the uppermost pile by 0.08 cm, 0.16 cm and 0.29 cm. While the results of the lateral deflection analysis of the manual calculation of the p-y curve method with a finite different up to 25 kN, 50 kN, and 75 kN loads obtained lateral deflection of the uppermost pile respectively by 0.60 cm, 0.12 cm and 0.179 cm. So the approximating calculations are manual calculation of the p-y curve method with calculations with Allpile software. Nash-Sutcliffe Efficiency (NSE) value calculation of the p-y curve method with plaxis software at lateral load 25 kN, 50 kN, 75 kN obtained consecutive NSE values of -5,946, -6,439, dan -30,118 all of which have unsatisfactory performance rating. Different with curve p-y method compared with Allpile that has consecutive NSE values of 0,876, 0,876, 0,876, dan 0,605 all of which have very good performance rating. ABSTRAKSalah satu jenis fondasi dalam adalah fondasi tiang yang didesain dan memiliki kemampuan untuk menahan beban aksial, lateral, dan uplift. Analisis ini bertujuan untuk mengetahui dan membandingkan defleksi yang terjadi pada tiang yang berada pada tanah granuler dengan menggunakan perhitungan manual metode kurva p-y dengan pendekatan beda hingga dan perhitungan dengan software Allpile dan Plaxis. Analisis dilakukan tiga kali percobaan yaitu pada tiang berdiameter 60 cm pada kedalaman tiang tertanam 10 meter dengan beban lateral sebesar 25 kN, 50 kN, dan 75 kN. Data yang dipakai untuk menghitung defleksi lateral tiang adalah data sekunder. Analisis defleksi lateral menggunakan software Plaxis dengan beban 25 kN, 50 kN, dan 75 kN didapatkan defleksi lateral tiang paling atas berturut-turut sebesar 0,159 cm, 0,324 cm, dan 0,545 cm. Analisis defleksi lateral menggunakan software Allpile dengan beban 25 kN, 50 kN, dan 75 kN didapatkan defleksi lateral tiang paling atas berturut-turut sebesar 0,08 cm, 0,16 cm, dan 0,29 cm. Sedangkan hasil analisis defleksi lateral perhitungan manual metode kurva p-y dengan pendekatan beda hingga dengan beban 25 kN, 50 kN, dan 75 kN didapatkan defleksi lateral tiang paling atas berturut turut sebesar 0,60 cm, 0,12 cm, dan 0,179 cm. Jadi perhitungan yang saling mendekati adalah perhitungan manual metode kurva p-y dengan perhitungan dengan software Allpile. Perhitungan nilai Nash-Sutcliffe Efficiency (NSE) metode kurva p-y dengan software Plaxis pada beban lateral 25 kN, 50 kN, dan 75 kN didapatkan nilai NSE berturut-turut sebesar -5,946, -6,493, dan -30,118 yang ketiganya memiliki rating performa tidak memuaskan. Berbeda dengan metode kurva p-y dibanding dengan Allpile memiliki nilai NSE berturut-turut sebesar 0,876, 0,876, dan 0,605 ketiganya mempunyai rating performa yang sangat baik.